APPLICATION OF ROY'S ADAPTATION OF NURSING THEORY TO CORONARY HEART DISEASE (CHD) CLIENTS IN THE INTENSIVE CARE UNIT - moch, bahrudin; dari, tanty wulan (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2023)
Miokard infark estimated one of the root cause death at 2020, disease of cardiovaskuler result death 25 million patient every year him. Medication of principal miokard infark is reperfusi by using drug of tromboliosis or wear mechanical way that is with intervention of kateterisasi heart is so called Percutaneous transluminal coronary Angioplasty (PTCA) pass/through puff (balloning) or installation of prop ( stent). Reperfusi done in intensive care unit to facilitate monitor growth of client. Acceptance of patient in intensive care unit is threat to prosperity and life and also feel as sign will arrive death. Thereby will generate stress covering physical, psychology, social, and spiritual of finansial. Target of this writing is to give more comprehensive picture to applying of theory and concept adaptation Roy in giving treatment upbringing patient of miokard infark which in taking care of intensive treatment. Concept and especial treatment theory the applied is adaptation according to Roy, because client of miokard infark which was risk the happening of death, this matter is stressor needing mechanism of koping. Nurse assist to develop ability of adaptation to stressor. Other concept the supporting is caring of Watson. Through applying of concept, can improve optimal health for client of miokard infark so that health can be defended.